Terminometry - how termish is a term? - Blom, Bjarne (HERMES - Journal of Language and Communication in Business, 2017)
Is a term merely a term, or are some terms more termish than others? This is the fundamental underlying theoretical question of the present study of the terminology of the Danish VAT act. The introduction of the concept "termhood" provides for term differentiation in terms of degree. Termhood allows us to determine whether for example “VAT exempt goods” is more termish than “taxable person” within the context of VAT legislation .